Psychometrics, Rhetoric, Narrative in Media Psycholinguistics - Karpenko, Zinoviia (Lesya Ukrainka Volyn National University, 2020)
The paper is focused on the critical exploration of an experiment held in the Ukrainian media environment. The results of the experiment are reflected in the book Freedom of Speech Against Fear and Humiliation published by Savik Shuster (2018), the Ukrainian political journalist and the Freedom of Speech TV talk show host. The study aims to define factors and predictors of the Ukrainian audience’s social behavior. In this regard, narrative, conversational, and intent analyses of his talk show participants’ conflict interaction described in the book, were applied. These tools made it possible to explicate his narratives’ main topics, their prominence, role positions, archetypal patterns of the participant, and host’s behavior. The narrative structure of “negative” scenarios of the talk show described in the book enabled defining the host as the encourager of the speakers’ conflict behavior, high tension of their discourse that leads to deconstructing, discrediting, and demonizing the opponent’s political party image. Although Schuster's conclusions were full of dramatic statements and almost apocalyptic predictions, their reinterpretation was necessary. The application of F-test as a measure of testing statistical hypotheses relevant to empirical data, allowed to search for additional political and psychological explanatory models of the “emotional map of Ukraine”. The results of the study demonstrate hidden suggestion of hopelessness, feelings of betrayal, protest moods inspired by the speakers invited to the TV show. This adversely affects the critical understanding of current social processes along with the radicalization of public sentiment by shifting the locus of control to the outside, when the audience invited to the show delegates responsibility for the state of affairs in the country and their own well-being to their political leaders.
Keywords: narrative; media; individual behavior; conversational analysis; intent analysis; mass emotions